Relative exercise intensity of a Krankcycle workout - Boyer, Blake (My University, 2009)
Purpose: The purpose of this study was to determine the relative exercise intensity and caloric expenditure of a 30-minute Krankcycle workout. Methods: Twelve physically active subjects age 23.8 2.60 years volunteered for the study. Subjects performed three 15-minute practice trials and a maximal exercise test on the SCIFIT upper body ergometer (Tulsa, Oklahoma) to find HRmax, VO2max, and the HR/VO2 relationship. HRmax (179 14.0 bpm) was measured with a Polar monitor while VO2max (34.7 7.15 ml/kg/min) was measured continuously on an AEI metabolic system (Naperville, Illinois). Subjects then performed a 30-minute instructor-led Krankcycle workout. HR and RPE were measured during the workout. Results: The average HR for the trial was 154 10.0 bpm, corresponding to 86 4.0 % HRmax. The average VO2 for the workout was 25.0 5.90 ml/kg/min, relating to 72 10.0 % VO2max. On average subjects burned 9.0 Kcal/min, 269 Kcal total, and spent approximately 90% of the time above 70% HRmax during the trial. Conclusions: It is concluded that a 30-minute Krankcycle workout is of moderate to very high intensity, and is capable of eliciting high enough HR and VO2 values to cause cardiovascular and body composition changes.
Keywords: Isometric exercise -- Physiological aspects; Arm exercises -- Physiological aspects